Foreign investors versus host communities: an urban political economy model for tourist cities - Sheng, Li; Gao, Jie (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
By developing an urban political economy model for tourist cities that considers the side effects and a city’s carrying capacity for tourism, this paper shows how foreign investors and a host community’s interests and preferences on the openness of the city greatly diverge. Foreign investors have the tendency to influence a city’s policy toward more openness than optimal. If foreign investors’ interest is overly represented in a city’s policymaking, the city may not be able to a follow a rational development strategy. Macao is adopted as a case study
Argumenta Oeconomica, 2018, Nr 2 (41), s. 257-275
Keywords: foreign investor; host community; side effects; bargaining